(untitled) - Narison, Stepphan (United Kingdom, 2004)
This book reviews the historical development of the subject up to the present day, covering aspects of strong interactions such as the quark and parton models, the notion of colours and the S-matrix approach. The author then discusses QCD and QED as gauge theories, renormalization procedures, QCD hard processes in hadron collisions, hadron jets, and the different non-perturbative aspects of QCD
Keywords: Quantum chromodynamics,Sắc động học lượng tử,Hạt cơ bản